# How to solve $\frac{d^{2}y}{dx^2} + \frac{1}{x} \frac{dy }{dx} =0$? [closed]

Let $y\in C^{2}(\mathbb R)$ (twice continuously differntiable function). We consider the ODE as follows: $$\frac{d^{2}y}{dx^2} + \frac{1}{x} \frac{dy }{dx} =0$$ ($y$ is function of $x$)

My naive question is: (1) How to solve the above ODE? (2) How to make this question rigorous? (What can we say about solution, etc....)

## closed as off-topic by Travis, Bumblebee, TravisJ, Tim Raczkowski, Zain PatelJul 21 '15 at 16:56

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Travis, Bumblebee, TravisJ, Tim Raczkowski, Zain Patel
If this question can be reworded to fit the rules in the help center, please edit the question.

• Did you notice that there is no $y$ in equation? Just put $v=dy/dx$, and you get a separable first order equation. – orion Jul 21 '15 at 7:33

## 4 Answers

Write the ODE as $$xy''+y'=0$$ Where prime dentoes derivative wrt to $x$. Then notice the left hand side is simply the derivative of a product, so $$(xy')'=0$$ By implication therefore $$xy'=C$$ Where $C$ is a constant; thus $$dy=\frac{C dx}{x}$$

HINT: Try to make change of variables

\begin{aligned} u = \frac{dy}{dx} & \implies \frac{du}{dx}=\frac{d^{2}y}{dx^{2}} \implies \boxed{\frac{d^{2}y}{dx^2} + \frac{1}{x} \frac{dy }{dx} =0 \iff \frac{d u}{dx} + \frac{1}{x} u =0} \end{aligned}

Note that the resulting differential equation $$\frac{d u}{dx} + \frac{1}{x} u = 0$$ is separable, so you can easily integrate it and find its solution $u = u(x)$, and consequently $y = y(x)$.

First note that $\color{blue}{y_1=1}$ is a solution, if you are looking for a second solution $y_2$ for an homogeneous ODE $$y''+p(x)y'+q(x)=0...(1)$$ you can use the formula $$y_2=y_1\int\frac{e^{-\int p(x)dx}}{y_1^2}dx$$ The general solution for $(1)$ can be written as $y(x)=c_1y_1+c_2y_2$ where $c_1$ and $c_2$ are constants.

• As far as theory goes - this is the best approach in my opinion. +1 – Autolatry Jul 21 '15 at 8:18

In general this is the Cauchy equation. The general method is to use the transformation $y=x^m$ for some integer $m$. Though for the present case if you simply take $p=dy/dx$ you'll get $$d(\ln p)/dx+1/x=0$$ which can be easily solved to obtain $p x=C\implies dy=C\frac{dx}{x}\implies y=C\ln x+D$.